Power Influence Towards Society Protest Behavior Around The Extractive Petroleum Industry - Nadya Izana, Nyimas; K. Pandjaitan, Nurmala (Sodality: Jurnal Sosiologi Pedesaan, 2015)
One of the extractive petroleum industries that are currently present in Indonesia is the PCI Industry which cooperates with Pertamina. PCI Industry is located in Bojonegoro, East Java and established in 2002. Ever since the presence of the extractive petroleum industry, conflict with society is started to begin. The method used in this study was a quantitative method that was supported by quantitative data. Qualitative data were obtained by observations and in-depth interviews. Quantitatif data using questionnaires were obtained from two  villages  with  100  respondents.  Respondents  were  divided  into  two  geoups:  responden  who  did  non participate in the protest and respondents who participated in the protest.This study aims to analyze the root problem of public protest occurence towards the PCI Industry, analyze the presence of PCI Industry that raises a certain protest behavior of society and analyze the effect of local leaders power on the dynamics and behavior of the society protest. The result showed that the  root problem of public protes occurence towards the PCI Industry  is an opportunities to work in the PCI Industry, CSR funds, environmental demanding.  The protest behavior of local people due to the presence of the PCI Industry is in accordance with the theory of planned behavior which mentions that attitude is not enough to determine behavior, but there are subjective norms and perceived behavioral control. The effect of local leader power on the dynamics and behavior of the society protest is appreciable.  Keywords:  attitudes, behavior control, power, subjective norms, work and business opportunities